The Analysis of Cold Chain Management of Basic Immunization Vaccine in Health Service Centers, 2018 - Wetra Fauza; Firdawati Firdawati; Rosfita Rasyid (Jurnal Berkala Epidemiologi, 2019)
Background: Vaccines are biological products that promote immunity activation in children. Vaccines content are susceptible and need more treatment in temperature (20C-80C), storage, and use during the delivery process to health service centers. Purpose: This study aims to determine the cold chain management of basic immunization vaccine in health service centers, South Solok Regency. Method: This research is a qualitative study. The sampling is done by using purposive sampling technique. This research was carried out at the health service center in South Solok Regency. This study uses primary and secondary data sources. The source of primary data is taken by in-depth interviews, while secondary data comes from document review and observations of data in 2018. Source and methodological triangulation were performed in this study. Results: The availability of human resources, funds, facilities and infrastructure and work procedures are sufficient, although there is still one untrained health service center staff, lack of vaccine flasks in two health service centers, and lack of voltage stabilizers in seven health service centers. Almost all health service centers have been applied vaccine boxes 20C-80C in vaccine transportation system. Based on the evaluation, only one health service center that need to improve especially in temperature evaluation procedure by thermometer. The vaccine storage procedure has been applied by the health service center. However, the observation noticed three health service centers have problems in time delay in the melting process. Conclusion: The management of the cold chain vaccine in the health service center, South Solok Regency is good.